2019
DOI: 10.1186/s13567-019-0649-8
|View full text |Cite
|
Sign up to set email alerts
|

Spleen and head kidney differential gene expression patterns in trout infected with Lactococcus garvieae correlate with spleen granulomas

Abstract: Lactococcus garvieae is a significant pathogen in aquaculture with a potential zoonotic risk. To begin to characterize the late immune response of trout to lactococcosis, we selected infected individuals showing clinical signs of lactococcosis. At the time lactococcosis clinical signs appeared, infection by L. garvieae induced a robust inflammatory response in the spleen of rainbow trout, which correlated with abundant granulomatous lesions. The response in kidney goes in para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 40 publications
1
17
0
Order By: Relevance
“…The reason for this remains unknown, but A. salmonicida and A. hydrophila also increase the expression of hepc in various immune tissues of sharp-snouted lenok ( Brachymystax lenok ) and brown trout [ 13 , 25 ]. A plethora of AMPs, including hepc , are differentially expressed in immune organs such as the spleen and head kidney of rainbow trout infected with L. garvieae [ 38 ]. Interestingly, in silico target prediction of the spleen and head kidney of Atlantic salmon during infection with P. salmonis , an intracellular bacterium, revealed hepc1 as a target of select miRNAs [ 39 ].…”
Section: Factors Affecting Salmonid Amp Gene Expressionmentioning
confidence: 99%
“…The reason for this remains unknown, but A. salmonicida and A. hydrophila also increase the expression of hepc in various immune tissues of sharp-snouted lenok ( Brachymystax lenok ) and brown trout [ 13 , 25 ]. A plethora of AMPs, including hepc , are differentially expressed in immune organs such as the spleen and head kidney of rainbow trout infected with L. garvieae [ 38 ]. Interestingly, in silico target prediction of the spleen and head kidney of Atlantic salmon during infection with P. salmonis , an intracellular bacterium, revealed hepc1 as a target of select miRNAs [ 39 ].…”
Section: Factors Affecting Salmonid Amp Gene Expressionmentioning
confidence: 99%
“…Likewise, an intense expression of lep and lepr was observed in spleen and head kidney of C. punctata though the pattern varied from secondary to primary lymphoid organ. Recent studies in fishes have also shown marked difference between spleen and head kidney with respect to expression pattern of immune-related genes and their respective proteins in response to bacterial infection [34][35][36] . These differences have been attributed to differential role of primary and secondary lymphoid organs as teleostean spleen is proposed to be majorly involved in cellular responses while head kidney in humoral responses 34 .…”
Section: Discussionmentioning
confidence: 99%
“…(P erez-Arellano & del Pozo 2013). These bacteria have been subject to further study, identified and used in experimental models to explain the underlying mechanisms in granulomatous processes; however, other bacteria apart of these can be also found in literature as etiological agents of granulomatuos diseases (Table 1); for example, Lactococcus garvieae, which is associated with fatal haemorrhagic septicaemia in farmed rainbow trout (Shahi et al 2018), can also produce spleen granulomas while inducing antibody response by both IgM (+) and IgT (+) spleen B cells (Castro et al 2019).…”
Section: Granulomatous Infections In Fishmentioning
confidence: 99%